2015
DOI: 10.4103/0974-2069.149515
|View full text |Cite
|
Sign up to set email alerts
|

Aortopathy associated with congenital heart disease: A current literature review

Abstract: In patients born with congenital heart disease, dilatation of the aorta is a frequent feature at presentation and during follow-up after surgical intervention. This review provides an overview of the pathologies associated with aortopathy, and discusses the current knowledge on pathophysiology, evolution, and treatment guidelines of the aortic disease associated with congenital heart defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
4

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 103 publications
(141 reference statements)
1
35
0
4
Order By: Relevance
“…A longer follow‐up period was also significantly correlated with the presence of ARD in both ARD definitions. The prognosis after surgical repair of uncomplicated VSD is excellent, with a reported 25‐year survival rate after surgical VSD repair of 89% . This suggests that long follow‐up periods are not rare in patients with surgically repaired VSD; hence, physicians should perform cardiovascular imaging to detect potential aortopathies, such as ARD .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A longer follow‐up period was also significantly correlated with the presence of ARD in both ARD definitions. The prognosis after surgical repair of uncomplicated VSD is excellent, with a reported 25‐year survival rate after surgical VSD repair of 89% . This suggests that long follow‐up periods are not rare in patients with surgically repaired VSD; hence, physicians should perform cardiovascular imaging to detect potential aortopathies, such as ARD .…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis after surgical repair of uncomplicated VSD is excellent, with a reported 25‐year survival rate after surgical VSD repair of 89% . This suggests that long follow‐up periods are not rare in patients with surgically repaired VSD; hence, physicians should perform cardiovascular imaging to detect potential aortopathies, such as ARD . Additionally, atherosclerotic risk factors (eg, obesity and hypertension) are frequent in adults with congenital heart disease as well as the general population .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 A few cases of dissection of the aorta or progressive aortic dilation with valvular regurgitation have been published. 4,5 When volume loading and hypoxia persist for a considerable period, and the time since Fontan procedure is long, or when the aortic valve is bicuspid, the aortic root may become dilated and result in aneurysmal changes.…”
Section: Images In Cardiovascular Medicine Murakami T Et Almentioning
confidence: 99%
“…regurgitation (AR) occur, resulting in a negative impact on systemic ventricular function, has been recognized in some CHD including coarctation of the aorta, bicuspid aortic valve, and conotruncal abnormalities such as tetralogy of Fallot. 3 Increasing evidence has suggested that functional single ventricle after Fontan procedure should be categorized as an aortopathy. 3-5 Herein we report the case of an adult after Fontan procedure for TA and LVNC in whom surgical intervention was necessary due to a progressively dilated aorta with AR.…”
Section: Disclosuresmentioning
confidence: 99%